2019
DOI: 10.1002/prot.25680
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heterochiral inversions on the structure of a β‐hairpin peptide

Abstract: We study computationally a family of β‐hairpin peptides with systematically introduced chiral inversions, in explicit water, and we investigate the extent to which the backbone structure is able to fold in the presence of heterochiral perturbations. In contrast to the recently investigated case of a helical peptide, we do not find a monotonic change in secondary structure content as a function of the number of L‐ to D‐inversions. The effects of L‐ to D‐inversions are instead found to be highly position‐specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 80 publications
1
7
0
Order By: Relevance
“…Accordingly, these authors have concluded that an apparent increase in structural order occurs in the retro-inverso form of the peptide compared to the normal form [55]. Our findings showing increased structural order upon retro isomerization of p53 are, therefore, qualitatively consistent with Lu and coworkers' experimental results, insofar as quantitative measures of structural properties that are insensitive to chirality must be the same between chirally inverted peptides (such as retro and retro-inverso forms of the p53 fragment), while the ones sensitive to chirality must be exact mirror images of those of the parents [11,12,61]. Our results emphasize that secondary structure is a strong function of backbone directionality for sufficiently long peptides, even if the secondary structure is only local, as in the p53 15-29 peptide.…”
Section: Linear Peptidessupporting
confidence: 91%
“…Accordingly, these authors have concluded that an apparent increase in structural order occurs in the retro-inverso form of the peptide compared to the normal form [55]. Our findings showing increased structural order upon retro isomerization of p53 are, therefore, qualitatively consistent with Lu and coworkers' experimental results, insofar as quantitative measures of structural properties that are insensitive to chirality must be the same between chirally inverted peptides (such as retro and retro-inverso forms of the p53 fragment), while the ones sensitive to chirality must be exact mirror images of those of the parents [11,12,61]. Our results emphasize that secondary structure is a strong function of backbone directionality for sufficiently long peptides, even if the secondary structure is only local, as in the p53 15-29 peptide.…”
Section: Linear Peptidessupporting
confidence: 91%
“…Establishing differences in the properties of L-and D-tryptophan (Trp) which are part of various proteins, enzymes, and receptors is an important fundamental and practical problem, as the optical isomers themselves are identical in physicochemical properties, while proteins containing L-and D-isomers of amino acids, in particular, Trp, are dramatically different [1]. Thus, chiral inversion, which as is known, occurs during aging of living organisms and leads to the replacement in a number of proteins L-isomers of amino acids with D-analogs, is currently considered one of the main causes of Alzheimer's, Parkinson's, type II diabetes, and a number of other pathological conditions [1,2]. Due to the difficulties arising in the study of these highly disordered proteins by modern physicochemical methods, including high-resolution NMR spectroscopy, the model systems are proposed for studying the reasons of the abnormal behavior of proteins with D-optical isomers of amino acids [3].…”
Section: Introductionmentioning
confidence: 99%
“…(It is important to note that free energy profiles and barriers may be influenced by degrees of freedom that are orthogonal to the chosen order parameters . While the order parameters employed here, RMSD and number of native hydrogen bonds, have been successfully employed elsewhere, an interesting future direction might be to optimize their choice, using, e.g., kinetically selected collective variables. , ).…”
Section: Discussionmentioning
confidence: 99%
“…The other peptide, known as Tryptophan Zipper 4 (TZ4, GEWTWDDATKTWTWTE), differs from GB1 via three tryptophan substitutions, which enhance the hydrophobic stabilization of the folded state (Figure ). GB1 and TZ4 have been extensively studied by both experiment and simulation and are known to exhibit rapid, reversible, and cooperative folding; they are thus ideal model systems within which to investigate the influence of polyelectrolyte assembly on protein structure and stability. Owing to their previous success in enhancing protein conformational stability ,,, and their known biocompatibility, we consider the (cationic) polyelectrolytes poly­( l -lysine) (a poly­(amino acid)) and chitosan (a polysaccharide) (Figure ).…”
Section: Introductionmentioning
confidence: 99%